Literasi digital berbasis media interaktif untuk meningkatkan hasil belajar siswa generasi alpha di SDN 46 Songing - Muallim Muallim (Journal of Smart Education and Learning, 2026)
This study aims to describe how digital literacy contributes to improving the learning outcomes of Generation Alpha students at SDN 46 Songing. Generation Alpha (born around 2010 onwards) has grown up in a technology-rich environment; however, familiarity with digital devices does not necessarily indicate adequate digital literacy. In this study, digital literacy is defined as students’ ability to access, evaluate, and use digital information critically and responsibly. The research employed a qualitative, descriptive approach. Data were collected through classroom observations, structured interviews, and document analysis, including students’ academic score records, involving the principal, teachers, and students as informants. Data were analyzed inductively through data reduction, data display, and conclusion drawing, with credibility ensured through technique and source triangulation. The findings show that digital literacy was implemented through digital presentations (PowerPoint/Canva), audio-visual media (Smart TV/YouTube), and educational quizzes/games (Quizizz, Baamboozle). These practices increased student engagement, supported concept visualization, and positively influenced learning outcomes, although implementation was constrained by limited infrastructure and the need for teacher training.